Estimates of kinetic degradability parameters and passage of materials originated from intercropping of brachiaria grass and corn and soybean crops - Tadeu Silva de Oliveira; José Carlos Pereira; Ricardo Augusto Mendonça Vieira; Fernando de Paula Leonel; Marcelo Teixeira Rodrigues (Revista Brasileira de Zootecnia, 2011)
The study was conducted to determine the kinetic parameters of in situ DM and NDF and the passage of particles of forages produced from the intercropping of brachiaria grass with corn and soybean crops. Three experiments were performed, as follows: Experiment 1 - Brachiaria grass intercropped with corn at different plant ages; Experiment 2 - Cultivation of brachiaria grass intercropped with corn set in different sowing arrangements; and Experiment 3 - Intercropping of brachiaria grass and soybean. Passage kinetic of particles was determined by the recovery of markers in feces. In order to obtain the ruminal degradation of DM and NDF, nylon bags were used at zero time, 3, 6, 9, 12, 24, 48, 72, 96, 120 and 144 hours. The particles' passage kinetic of corn with brachiaria grass silage and brachiaria grass silage presented 3%/h and 2.3%/h, respectively; and for soybean and brachiaria grass silage, it was 1.8%/h, which can be explained in part by the mixture of materials ensiled. The materials originated from the intercropping caused rumen fill. Degradation rates were lower when compared with literature data. The brachiaria grass silage obtained from corn and/or soybean crop-pasture integrated system is a feed with low nutritive value due to its low NDF degradation rate and low passage rate, causing rumen fill and, thus, possibly resulting in low intake and poor animal performance.